2019
DOI: 10.1111/jam.14432
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the bacteria community in wild Cordyceps cicadae and its influence on the production of HEA and nucleosides in Cordyceps cicadae

Abstract: Aims The purpose of this study was to investigate the bacterial community of wild Cordyceps cicadae and explore its effect on the production of N6‐(2‐hydroxyethyl)‐adenosine (HEA) and three nucleosides in C. cicadae. Methods and Results Illumina high‐throughput sequencing technology was used to analyse the bacterial community in wild C. cicadae. After C. cicadae was isolated and bacteria were isolated from wild C. cicadae, we identified four bacterial strains that independently altered HEA and nucleoside produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…In addition, in this study, the sclerotia of C. cicadae cultivated in glass bottles was rich in Cedecea bacteria, but this genus had a very low relative abundance in sclerotia of C. cicadae cultivated in natural habitats. Previous researches isolated and detected Cedecea in C. cicadae ( Qu et al, 2019a , b ); however, another study did not detect any Cedecea in sclerotia of C. cicadae ( Mou et al, 2021 ), which indicated the abundance of Cedecea in C. cicadae is unstable and may be affected by the growth environment. Furthermore, in our study, bacterial community composition varied with the time point (and therefore growth stage) of C. cicadae , similar to previously published research ( Wu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, in this study, the sclerotia of C. cicadae cultivated in glass bottles was rich in Cedecea bacteria, but this genus had a very low relative abundance in sclerotia of C. cicadae cultivated in natural habitats. Previous researches isolated and detected Cedecea in C. cicadae ( Qu et al, 2019a , b ); however, another study did not detect any Cedecea in sclerotia of C. cicadae ( Mou et al, 2021 ), which indicated the abundance of Cedecea in C. cicadae is unstable and may be affected by the growth environment. Furthermore, in our study, bacterial community composition varied with the time point (and therefore growth stage) of C. cicadae , similar to previously published research ( Wu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 97%
“…Previous research found that the composition of microbial communities in host varies between different growth environments ( Mueller et al, 2020 ), and changes in microbial community composition in Cordyceps spp. can affect growth and metabolite production of host ( Zhang et al, 2010 ; Qu et al, 2019a , b ). Cultivating C. cicadae in natural habitats, rather than under sterile conditions, may therefore be a helpful experimental approach to exploring soil microbial interactions and their potential impact on growth and metabolite production in C. cicadae .…”
Section: Introductionmentioning
confidence: 99%
“…Antagonism is the most common relationship between macrofungi living in nature, which combat via cell-cell contact or form a confrontation zone due to the production of antimicrobial substances or chemical signals, such as in relationships between Cordyceps cicadae and many of its endophytic bacteria (Qu et al, 2019). The appearance of confrontation zones usually indicates the induction of bioactive substances and their release to inhibit competitors.…”
Section: Interactions Of Macrofungi In Naturementioning
confidence: 99%
“…Cordyceps cicadae as an ascomycete fungus is parasitic in the larvae of Cicada flammata and can produce diverse compounds such as N6-(2-hydroxyethyl)-adenosine (HEA) (36) (Table 1), adenosine, ergosterol, and cordycepin to improve immune regulation and renal function. Fifty-four endophytic bacteria were isolated along with C. cicadae, and four of them were chosen to be cocultured with C. cicadae according to metabolite analysis and their inhibitory phenomena (Qu et al, 2019). Coculture was performed with C. cicadae precultured for 5 days before inoculating bacteria (including Enterobacter aerogenes T4-4, Serratia marcescens T4-16, Cedecea neteri T4-8, and T4-11).…”
Section: Cocultures Of Macrofungi and Bacteria Or Macrofungi And Actinomycetesmentioning
confidence: 99%
See 1 more Smart Citation